Pengembangan Permainan Edukatif Ular Tangga “Eduta” Untuk Menstimulasi Aktivitas Gerak Anak Usia 5-6 Tahun - Maryamah, Elisa; Pramono; Tirtaningsih, Munaisra Tri (Universitas Pahlawan Tuanku Tambusai, 2024)
Snakes and ladders game is a board game divided into several boxes and in the box contains a picture of a number of ladders and snakes that connect to other boxes using ball numbers to determine how many steps the pieces must take. The purpose of the study was to determine the ability of children's motor activity through educational games and the feasibility of the educational game snakes and ladders